2013
DOI: 10.1111/j.1948-7134.2013.12042.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood, sweat, and tears: a review of the hematophagous, sudophagous, and lachryphagous Lepidoptera

Abstract: Although adult Lepidoptera are not often considered medically relevant, some butterflies and moths are notorious for their consumption of mammalian body fluids. These Lepidoptera can be blood-feeding (hematophagous), tear-feeding (lachryphagous), or sweat-feeding (we use the term "sudophagous"). Blood-feeding Lepidoptera have been observed piercing the skin of their hosts during feeding, while tear-feeding Lepidoptera have been observed frequenting the eyes of hosts in order to directly obtain lachrymal fluid.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 14 publications
0
16
0
1
Order By: Relevance
“…To compensate for the lack of a particular nutrient, insects may acquire these through supplementary feeding on e.g., mud, various excrements and secretions of vertebrates, and carrion, in a process referred to as puddling (Molleman, 2010). Although mainly described for various butterfly and moth species, puddling also occurs in other insect orders, where attraction to and feeding on these types of resources has a significant effect on fitness and other life-history traits (Bänziger et al, 2009;Hendrichs et al, 1993;Molleman, 2010;Plotkin and Goddard, 2013;Shen et al, 2009). The malaria mosquito, Anopheles gambiae sensu lato, ecloses as an 'undernourished' adult (Van Handel, 1965), and, as such, puddling may play an important role for its life-history traits, but is a behaviour that so far has been overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…To compensate for the lack of a particular nutrient, insects may acquire these through supplementary feeding on e.g., mud, various excrements and secretions of vertebrates, and carrion, in a process referred to as puddling (Molleman, 2010). Although mainly described for various butterfly and moth species, puddling also occurs in other insect orders, where attraction to and feeding on these types of resources has a significant effect on fitness and other life-history traits (Bänziger et al, 2009;Hendrichs et al, 1993;Molleman, 2010;Plotkin and Goddard, 2013;Shen et al, 2009). The malaria mosquito, Anopheles gambiae sensu lato, ecloses as an 'undernourished' adult (Van Handel, 1965), and, as such, puddling may play an important role for its life-history traits, but is a behaviour that so far has been overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…ages, free-ranging animals often consume a variety of mineral-rich items that are not considered normal dietary items for the species, including soil, termite mounds, animal tears, mineral spring water, plant vegetative parts (leaves, trunks, bark, etc. ), and others (Mahaney et al 1996, Reynolds et al 2009, 2015, Overton et al 2010, Brightsmith & Villalobos 2011, Plotkin & Goddard 2013.…”
mentioning
confidence: 99%
“…In these events, the moths insert their morphologically adapted proboscis (Zaspel et al 2011) on the target species' ocular area to feed on their tears (Hilgartner et al 2007, Zenker et al 2011. Although one currently known moth is an obligatory lachryphagous species (Waage 1979), most of them feed on tears as a supplementary method to obtain nutrients, mainly sodium and proteins (Plotkin and Goddard 2013). This biotic interaction is well reported between moths and mammals, as well as between moths and turtles or crocodiles (B€ uttiker 1964, 1997, Downes 1973, B€ anziger 1987, 1990, 1992, Plotkin and Goddard 2013, but very few events are known involving the interaction between lachryphagous moths and birds (Sazima 2015).…”
mentioning
confidence: 99%
“…Although one currently known moth is an obligatory lachryphagous species (Waage 1979), most of them feed on tears as a supplementary method to obtain nutrients, mainly sodium and proteins (Plotkin and Goddard 2013). This biotic interaction is well reported between moths and mammals, as well as between moths and turtles or crocodiles (B€ uttiker 1964, 1997, Downes 1973, B€ anziger 1987, 1990, 1992, Plotkin and Goddard 2013, but very few events are known involving the interaction between lachryphagous moths and birds (Sazima 2015). Hilgartner et al (2007), first showed that the moth Hemiceratoides hieroglyphica (Saalm€ uller 1891) (Erebidae) feeds on the tears of a Common Newtonia Newtonia brunneicauda (Newton 1863) (Vangidae) and a Madagascar Magpie-robin Copsychus albospecularis (Eydoux & Gervais 1836) (Muscicapidae) in Madagascar, Africa.…”
mentioning
confidence: 99%